Grafting Durian Seedlings (Durio zibethinus Murr.) Using the P1-P5 Technique - Ananto; Ecil Hasanah; Atika Mariana (Nusantara Science and Technology Proceedings, 2023)
This research purpose to determine the effect of several scions with different numbers of leaves using the P1-P5 technique. This research used a Completely Randomized Design (CRD) consisting of 5 treatment levels and 3 replications to obtain 15 experimental units. Each experimental unit consisted of 5 stems, so a total of 45 stems. Treatment consisted of P1 (leaf shoot 1), P2 (leaf shoot 2), P3 (leaf shoot 3), P4 (leaf shoot 4), P5 (leaf shoot 5). The observations observed were the number of leaves, leaf width, and percentage of life. The observations were analyzed by means of variance, if the F count from the F table was 5%, then further testing was carried out with the Duncan New Multiple Range Test (DNMRT) at the 5% level. The results of the research can conclude that grafting durian shoots using the P5 technique is the best technique for growth and grafting success.